Anemia infecciosa das galinhas em Minas Gerais: diversidade genética e epidemiologia molecular - Sandra Yuliet Marin Gomez (2012)
A study of the occurrence of chicken anemia virus (CAV) in broiler and layer chickens of the poultry industry, backyard chickens, and as a contaminant in commercial vaccines for chickens was carried out. The study was conducted in 2006-2011 and included 74 industrial poultry farms, being 54 broiler and 20 layer chickens, and 74 properties of backyard poultry, in different localities in the state of Minas Gerais, with and without clinical signs of disease. Commercial poultry vaccines (n=40) were also investigated. CAV DNA was detected by semi-nested PCR in 36.4% of industrial poultry farms, in 35% of the properties of backyard chickens and in 17.5% of live vaccines against avian encephalomyelitis, Mareks or Newcastle disease. CAV genetic regions that encode part of the VP1 protein, found in samples of ten farms from the poultry industry, and in seven properties of backyard chickens, were amplified, producing fragments of 1,271 nucleotides and were sequenced. The nucleotide sequences showed similarities from 93.7 to 99.5%, as compared with 20 sequences from different parts of the world in GenBank, and the deduced amino acid similarity ranged from 96.6 to 100%. In sequences of three strains obtained from broilers of regions Zona da Mata and the metropolitan region of Belo Horizonte (Minas Gerais), the amino acid F was found at position 98, substitution which appears to be typical of Brazilian strains. Amino acid substitutions were observed in the residues of positions 22, 75, 97, 139, 144, 287 and 370 of the CAV VP1 gene. The high rates of occurrence, similar to previous studies, here additionally demonstrated to be at similar rates in industrial and free-range chickens, may be indicative of CAV circulation among different poultry activities in Minas Gerais. The presence of CAV contaminant in vaccines may have been a complicating factor in CAV epidemiology, favoring dissemination and diversity. The chicken status and vaccine contamination results may have represented key factors in the epidemiologic history of CAV.